Experiencing Museum: Eksplorasi Digital Free Tourism di Museum Ullen Sentalu, Yogyakarta - Nisa, An Nuur Khairune; Fadin, Delfyan Intan Nurmala; Gustiarti, Putrisari Oktaviani (JURNAL NASIONAL PARIWISATA, 2023)
This research explores the concept of Digital Free Tourism (DFT) in the context of 'experiencing museum' in Ullen Sentalu. This study aims to analyze the application of the DFT concept in Ullen Sentalu Museum, Yogyakarta, as well as its implications for the museum's tourism experience. This research uses qualitative methods with an exploratory study approach conducted with data collection methods, namely observation, in-depth interviews, and literature studies collected from journals, books, articles, and also the Ullen Sentalu museum page. The results of this study found that the Ullen Sentalu Museum successfully applied the DFT concept by controlling the use of on-site technology during museum tours to maintain the safety of the collection and create a more immersive 'museum experience' and increase visitor curiosity and wellbeing. Ullen Sentalu also does not reject digital utilization but continues to innovate by optimizing digital content during pre-site and post-site to reflect his commitment to be relevant in the digital era while maintaining traditional values in DFT.